ASWAJA Ke-NUan-BASED ISLAMIC MODERATE EDUCATION AS A RADICALISM STRATEGY - Ari Kartiko; Muhammad Mujtaba Mitra Zuana; Akhmad Sirojuddin; Muhammad Huusnur Rofiq; Muhammad Anas Maarif (Fakultas Agama Islam Universitas Wiralodra, 2020)
This study aims to rationalize the Aswaja-based Islamic education strategy to counter radicalism. This research method uses literature by analyzing published, unpublished books, journals and research that are in line with the theme of moderate Islamic education through NU-an Aswaja. The results of this study are that NU implements an educational education commanded by LP Maarif NU and principled on al muhafadhotu ala al qodimi as sholih wal akhdu bil jadidi al aslah to aim at forming humans who are rahmatan lin naturalin. In learning the values that are strengthened and internalized are tawazun (balanced), tawassuh (moderate), i`tidal (fair and heartless) and tasammuh (tolerance).